In-silico design of curcumin analogs as potential inhibitors of dengue virus NS2B/NS3 protease - Roney, Miah; Huq, A. K. M. Moyeenul; Mohd Fadhlizil Fasihi, Mohd Aluwi; Saiful Nizam, Tajuddin (World Scientific Publishing Co Pte Ltd, 2023)
Curcumin can interact with a variety of molecules implicated in a wide range of disorders. It can also hinder dengue virus’s (DENV’s) ability to infect cells. This work used computational analysis to identify and forecast the most potent curcumin analogs against the DENV NS2B/NS3 protease. In this study, curcumin-like compounds were screened using a rational in-silico study, with the least similarity score, docking analysis, and then additional screening for suitable pharmacokinetic properties. According to the findings, DB11672 has been identified as the primary inhibitor of DENV NS2B/NS3 protease. It is recommended that additional research be done on this antiviral property of the lead compound as a part of the process of finding and developing a new drug against DENV.